Actinomyces odontolyticus: Rare Etiology for Purulent Pericarditis. (15th December 2014) - Mack, Ryan; Slicker, Kipp; Ghamande, Shekhar; Surani, Salim R.
Abstract : Purulent pericarditis is one of the most common causes of cardiac tamponade and if left untreated has a mortality of 100%. Staphylococcus aureus and Streptococcus pneumonia have been implicated as the main etiology of purulent pericardial effusion followed by fungi and anaerobic sources. Actinomyces odontolyticus pericardial involvement has been reported in the literature only once. To our knowledge, this is the first fatal case of A. odontolyticus purulent pericarditis in the absence of periodontal disease.